2016
DOI: 10.1128/mbio.00796-16
|View full text |Cite
|
Sign up to set email alerts
|

Exposing the Three-Dimensional Biogeography and Metabolic States of Pathogens in Cystic Fibrosis Sputum via Hydrogel Embedding, Clearing, and rRNA Labeling

Abstract: Physiological resistance to antibiotics confounds the treatment of many chronic bacterial infections, motivating researchers to identify novel therapeutic approaches. To do this effectively, an understanding of how microbes survive in vivo is needed. Though much can be inferred from bulk approaches to characterizing complex environments, essential information can be lost if spatial organization is not preserved. Here, we introduce a tissue-clearing technique, termed MiPACT, designed to retain and visualize bac… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
121
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
6
2
1

Relationship

1
8

Authors

Journals

citations
Cited by 125 publications
(127 citation statements)
references
References 55 publications
6
121
0
Order By: Relevance
“…While we are beginning to advance our knowledge of the distribution of microbial species during CF pulmonary infections, and how and to what extent interspecies interactions occur (50, 51), our understanding remains quite limited. We predict that in certain areas of the lung, P. aeruginosa and S. aureus are spatially segregated, which also likely contributes to S. aureus survival of during coinfection, independent of P. aeruginosa competitive phenotypes.…”
Section: Discussionmentioning
confidence: 99%
“…While we are beginning to advance our knowledge of the distribution of microbial species during CF pulmonary infections, and how and to what extent interspecies interactions occur (50, 51), our understanding remains quite limited. We predict that in certain areas of the lung, P. aeruginosa and S. aureus are spatially segregated, which also likely contributes to S. aureus survival of during coinfection, independent of P. aeruginosa competitive phenotypes.…”
Section: Discussionmentioning
confidence: 99%
“…Several studies have investigated the growth pattern of bacteria in the lungs of patients with CF. It is interesting that these studies have shown that species frequently classified as obligate aerobes, such as Staphylococcus aureus, Stenotrophomonas maltophilia, and Achromobacter xylosoxidans, exhibit virtually zero growth, which is in line with depletion of O 2 in infected parts of the CFs lungs, whereas the facultative anaerobe P. aeruginosa exhibits slow growth under these conditions (6,(55)(56)(57)(58). We conclude that PMNs apparently play a major role in modifying the chemical microenvironment thereby imposing growth restriction upon pathogens in biofilm aggregates associated with chronic lung infections of CF patients.…”
Section: Growth and Biofilm Structurementioning
confidence: 98%
“…HCR is a fluorescent in situ hybridization-like approach that includes a signal amplification step to help visualize low-abundant RNAs (8, 9). We previously used single HCR v2.0 probes to detect bacterial taxa in CF sputum samples (10), and HCR 2.0 was also used by Nikolakakis et al to detect host and bacterial mRNAs in the Hawaiian bobtail squid- Vibrio fischeri symbiosis (11). We chose to test HCR v3.0 as a tool to quantify bacterial gene expression in situ because of its improved specificity over HCR v2.0.…”
Section: Observationmentioning
confidence: 99%